Melatonin Enhances Seed Germination and Seedling Growth of Medicago sativa Under Salinity via a Putative Melatonin Receptor MsPMTR1 - Yu, Ruonan; Zuo, Tiantian; Diao, Pengfei; Fu, Jiabin; Fan, Yanyan; Wang, Yue; Zhao, Qiqi; Ma, Xuesong; Lu, Wenting; Li, Aoga; Wang, Ru; Yan, Fang; et al. (Frontiers in Plant Science, 2021)
Alfalfa (Medicago sativa L.) is an important forage crop, and salt stress is a major limiting factor in its yield. Melatonin (MT) is a multi-regulatory molecule in plants. We showed that basal MT content was positively correlated with the salt tolerance degree of different alfalfa varieties. MT and its precursor 5-HT fully recovered seed germination while partially ameliorated seedling growth of salt-stressed alfalfa. The 5-HT showed some divergent effects from MT with regards to growth amelioration under salinity. Salt stress caused stunted plant growth in soil culture, while MT ameliorated it by elevating plant height, fresh weight, branching number, and chlorophyll content. Silencing of a putative MT receptor, MsPMTR1, which was shown to be membrane-localized, abolished the ameliorative effects of MT on salt-stressed alfalfa seedling growth, while overexpression of MsPMTR1 improved plant growth under salt stress. The RNA sequencing analysis showed that nine pathway genes were specifically induced by MT treatment compared with salt stress. These MT-responsive differentially expressed genes include basal metabolic pathway genes, such as “ribosome, elongation factor,” “sugar and lipid metabolism,” and “photosynthesis” and stress-related genes encoding “membrane integrity” related proteins, heat shock protein, peroxidase/oxidoreductase, and protease. Several abiotic stress response-related genes, such as DRE, ARF, HD-ZF, MYB, and REM were repressed by NaCl treatment while induced by MT treatment. In summary, we demonstrated the importance of MsPMTR1 in MT-mediated salt tolerance in alfalfa, and we also analyzed the regulatory mechanism of MT during alfalfa seed germination under salt stress.